The excellent antitumor effect of apatinib alone as second-line therapy in a patient with sorafenib-refractory hepatocellular carcinoma: A case report. Issue 25 (June 2018) - Zhu, Hong; Ma, Xiaojun; Zhao, Yaqin; Duo, Ji
Abstract: Rationale: Hepatocellular carcinoma (HCC) is a highly invasive cancer associated with high mortality rates. Although sorafenib is currently recommended as standard treatment for advanced HCC, its treatment efficacy is limited. Effective treatments for patients with advanced HCC that progresses on or after sorafenib treatment or patients who are intolerant of sorafenib remain an unmet medical need. Patient concerns: We report an advanced HCC patient with many lung metastases who failed sorafenib treatment. Diagnoses: Sorafenib refractory HCC patient with a large number of lung metastases. Interventions: The apatinib alone was used as second line therapy. Outcomes: The patient achieved partial response (PR) soon after the treatment, which was maintained for approximately 1 year. During the entire process, the lung metastases continued to diminish. Finally, only a few lesions remained Lessons: Apatinib alone may be a good second-line therapy for advanced HCC patients who are refractory to sorafenib. However, further investigation in future prospective clinical studies is warranted.